Broadband deep‐red‐to‐near‐infrared emission from Mn2+ in strong crystal‐field of nitride MgAlSiN3. Issue 12 (23rd June 2020) - Liu, Shengqiang; Zhang, Shiyou; Mao, Ning; Song, Zhen; Liu, Quanlin
Abstract: Broadband near‐infrared (NIR) phosphors have received increasing attention for fabricating phosphor‐converted light‐emitting diodes (pc‐LEDs) as NIR light source. Most of the reported broadband NIR phosphors originate from Cr 3+ in weak crystal field environments. Herein, we report a luminescent material, MgAlSiN3 :Mn 2+ with CaAlSiN3 ‐type structure, demonstrating that broadband deep‐red‐to‐NIR emission can be achieved via doping Mn 2+ into crystallographic sites with strong crystal field in inorganic solids. This phosphor is synthesized via easy‐handle solid‐state reaction, and the optimized sample, (Mg0.93 Mn0.07 ) AlSiN3 shows an emission band with peak at ~754 nm, FWHM of 150 nm, and internal quantum efficiency of 70.1%. The photoluminescence intensity can further be enhanced by co‐doping Eu 2+ as sensitizer. This work provides a new strategy for discovering new broadband NIR phosphors using Mn 2+ in strong crystal field as luminescence center. Abstract : A new broadband deep‐red‐to‐NIR phosphor, MgAlSiN3 :Mn 2+ with CaAlSiN3‐type structure is reported. The novel deep‐red‐to‐NIR emission originate from Mn 2+ occupying Mg 2+ crystallographic sites with strong crystal‐field. Upon UV and visible light excitation, emission band maxima wavelengths can be tuned from 704 to 806 nm by changing Mn 2+ concentration. The optimal sample, (Mg0.93 Mn0.07 ) AlSiN3 shows emission band centered at ~754 nm with FWHM of 150 nm, and internal quantum efficiency of 70.1%. Furthermore, the luminescence intensity can be enhanced by using Eu 2+ as sensitizer. This work would motivate more study on using Mn 2+ as luminescent center to design and exploit new broadband NIR phosphors.